Redefining entrepreneurial happiness based on personality traits: the role of the Big Five - Gonzalez‑Peña, Anais Estefania; Sánchez Tovar, Yesenia; Galván Vela, Esthela; Ravina-Ripoll, Rafael (My University, 2025)
This study investigates how the Big Five personality traits shape the perception of happiness among Mexican entrepreneurs, addressing a gap in research on the psychological determinants of entrepreneurial well-being. A quantitative, cross-sectional survey was conducted with 319 entrepreneurs, and the data were analyzed using structural equation modeling. The results show that openness to experience, conscientiousness, and low neuroticism significantly increase perceived happiness, while agreeableness has no effect, challenging prior assumptions. These findings contribute to the literature by identifying personality-based predictors of entrepreneurial happiness and highlight the importance of psychological resources in entrepreneurship. In practice, the study offers insights for designing support programs and public policies that foster emotionally sustainable entrepreneurial ecosystems.
Journal of Innovation and Entrepreneurship
Keywords: Happiness; Big Five theory; Openness; Neuroticism; Conscientiousness; Campus Tijuana